DINAMIKA KELOMPOK PEMBUDIDAYA IKAN LELE SANGKURIANG (Clarias gariepinus) “DAMAI MAKMUR” DI KELURAHAN SIDODAMAI KECAMATAN SAMARINDA ILIR KOTA SAMARINDA - Norma; Helminuddin; Elly Purnamasari (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The purpose of this study is to examine the level of group dynamics of "Damai Makmur" Sangkuriang catfish (Clarias gariepinus) cultivators in Sidodamai Samarinda Ilir Samarinda. Primary data collection was carried out in June 2019 in Sidodamai Samarinda Ilir Samarinda. The sample was determined using census method, in which all of Sangkuriang Catfish (Clarias gariepinus) cultivator groups totaling 10 people became the respondents. The data was obtained by interview process using a list of questions. It was then analyzed descriptive-quantitatively based on the "Likert Scale", where each answer to the question was given a score, 3 as the highest score and 1 as the lowest score. The results showed that the level of group dynamics of "Damai Makmur" Sangkuriang Catfish (Clarias gariepinus) cultivators was in the high category (dynamic). Besides, for the group structure indicators, group effectiveness and group pressure result in the medium category (quite dynamic), while the hidden intention indicator is in the low category (not dynamic). Overall, the results of the level of group dynamics of the fish cultivators are in the high category with an average score of 116.4 in the range (113-144).